2022
DOI: 10.1016/j.jcmgh.2021.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocytes Are Resistant to Cell Death From Canonical and Non-Canonical Inflammasome-Activated Pyroptosis

Abstract: Caspase-1/11 activation induces macrophage pyroptosis, but hepatocytes are resistant to pyroptosis, which we show is mainly due to low levels of caspase-1/11 even after stimulation. Overexpression of caspase-1/11 p10/p20 can induce hepatocyte pyroptosis and cell shrinkage, but cell structure remains relatively intact differently from macrophage pyroptosis.CONCLUSIONS: Our novel findings characterize hepatocyte morphology in pyroptosis and suggest alternative use for canonical/non-canonical inflammasome activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Nevertheless, the mice we used were a whole-body Gsdmd knockout, which left some questions. Some researchers observed that hepatocytes are insensitive to pyroptosis, since GSDMD blockade in the innate immune cell protects against hepatic ischemia-reperfusion injury but the same was not true for hepatocytes ( 56 , 57 ). In contradiction, others demonstrated an essential role of GSDMD-mediated hepatocyte pyroptosis in acute liver failure ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the mice we used were a whole-body Gsdmd knockout, which left some questions. Some researchers observed that hepatocytes are insensitive to pyroptosis, since GSDMD blockade in the innate immune cell protects against hepatic ischemia-reperfusion injury but the same was not true for hepatocytes ( 56 , 57 ). In contradiction, others demonstrated an essential role of GSDMD-mediated hepatocyte pyroptosis in acute liver failure ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…The activated caspase-1, in turn, cleaves pro-IL-1β and pro-IL-18 into mature IL-1β and IL-18. Meanwhile, activated caspases can also cleave full-length GSDMD (GSDMD-FL) protein into N-terminal fragments of GSDMD (GSDMD‐NT), which exerts pore-forming function and leads to pyroptotic cell lysis (Song et al 2022 ; Sun et al 2022 ). Most recently, Kayagaki et al found that end‐stage plasma membrane rupture was not a passive osmotic lysis event but was dependent on ninjurin‐1 oligomerization (Kayagaki et al 2021 ).…”
Section: Molecular Mechanisms Of Pyroptosismentioning
confidence: 99%
“…The study concluded that pyroptosis plays an important role in the development of liver disease, including sepsis-induced liver injury [ 68 ]. Overexpression of the p10/p20 activation domain of caspase-1 or caspase-11 induces typical GSDMD-dependent pyroptosis in hepatocytes but not cell rupture after LPS stimulation in vitro and in vivo death is different [ 69 ]. In addition, Escherichia coli can also enter liver tissue and cause bacterial liver injury, and liver injury and pyroptosis are more severe in CD38 −/− mice, because CD38 deficiency triggers extracellular molecule recognition to activate inflammasome NLRP3-GSDMD-mediated Pyroptosis leads to severe bacterial liver damage [ 70 ].…”
Section: The Role Of Gsdmd In Sepsismentioning
confidence: 99%